Implementation of Chemo-entrepreneurship Through Project Based Learning to Determine the Level of Students' Soft Skills and Learning Motivation - Farah Diana; Abdul Gani; Muhammad Syukri; Arhamni Binti Hamid; Nurazidawati Mohamad Arsad (Journal of Science Learning, 2023)
Many factors in teaching chemistry influence students' soft skills and learning motivation. An attractive model is important in determining students' success in chemistry learning. This research aims to determine the level of soft skill abilities and students' learning motivation in implementing chemoentrepreneurship through project-based learning. The research methodology is quasi-experimental. In this study, 60 students were randomly selected from 162 MIPA class students who were grouped into 30 students in the experimental class and 30 in the control class. To determine the level of students' soft skill abilities and learning motivation, a survey was conducted on their learning activities. The N-gain value of learning motivation in the experimental class and control class was obtained at 0.68 and 0.40 (medium), while the N-gain value of soft skills was obtained at 0.63 (medium) and 0.28 (low). The percentage of learning motivation and soft skills in the experimental class with an average post-test of 84.68% and 80.54% (high), while in the control class with an average post-test of 73.53% and 68.33% (medium). The student soft skill and learning motivation hypothesis test findings show a substantial difference between the experimental and control classes.